Examination of the plum psyllid (Cacopsylla pruni Scopoli), a vector of European Stone Fruit Yellows (ESFY) phytoplasma in the countryside of Boldogkőváralja (Hungary) - Bodnár, Dominika; Mergenthaler, Emese; Viczián, Orsolya; Tarcali, Gábor (Acta Agraria Debreceniensis, 2019)
European Stone Fruit Yellows(ESFY) phytoplasma disease on apricot was identified by molecular methods for the first time in 1992 in Hungary. Currently, the pathogen is known as’ Ca. Phytoplasma prunorum’. Since, the pathogen become wide-spreaded and manyof the apricot-plantations had to be eliminated. In 2009 and 2010 in the countryside of Boldogkőváralja the infection of the apricot-plantations was about 77%. As the disease spreading and causing large damages, we studied the roleo fpossible vector,the plum psyllid (Cacopsylla pruni Scopoli) in the areas of Boldogkőváralja, North-East-Hungary. Studies were done in the year of 2016, monitoring the behaviour of the psyllids in four different areas, and caught 41 them for further examination. We collected plant samples from those apricot trees, on which the plum psyllids were caught.